1976
DOI: 10.1128/aac.10.4.776
|View full text |Cite
|
Sign up to set email alerts
|

New Medium for In Vitro Susceptibility Studies with Amphotericin B

Abstract: Antibiotic medium 20 FDA and antibiotic medium 3 FDA were compared to determine if antibiotic medium 3 would be suitable for in vitro susceptibility testing with amphotericin B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They suggested that this might indicate a difference in cell wall structure between the two forms. A-3 was originally described for susceptibility testing of yeasts with amphotericin B by Utz et al (18). We found that use of this medium enabled us to make clear-cut endpoint determinations.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…They suggested that this might indicate a difference in cell wall structure between the two forms. A-3 was originally described for susceptibility testing of yeasts with amphotericin B by Utz et al (18). We found that use of this medium enabled us to make clear-cut endpoint determinations.…”
Section: Methodsmentioning
confidence: 86%
“…A wide variety of newer antifungal agents have been tested, mainly in vitro, with varying degrees of success. Some, such as the nikkomycins (10,18) and polyoxins (1,14), inhibit chitin synthesis; the allylamines inhibit ergosterol synthesis in the cell membrane, thus affecting permeability. Examples of the allylamines are naftitine (15) and tolnaftate (8).…”
mentioning
confidence: 99%
“… 1 In the decade that followed its antifungal properties were recognized, and by 1968 flucytosine was used in humans for the treatment of candidiasis and cryptococcosis. 2 , 3 Flucytosine is a pyrimidine analogue that lacks intrinsic antifungal activity, but is taken up by susceptible fungal cells and deaminated intracellularly to its active metabolite, 5-fluorouracil, by fungal cytosine deaminase. 4 The further conversion of 5-fluorouracil produces metabolites that inhibit fungal RNA and DNA synthesis.…”
Section: Introductionmentioning
confidence: 99%